Analisis Gap dan Strategi Peningkatan Program Indonesia Pintar - Rahayu, Wiwiet Septiani; Nihayah, Dyah Maya (Universitas Negeri Semarang, 2020)
This study aims to determine the conditions and development of the application of the Smart Indonesia Program and strategies for improving the Smart Indonesia Program in Brebes Regency. This type of research is quantitative descriptive and qualitative descriptive. The data used are primary data. Respondents used in this study were 100 high school / vocational students who received the Indonesia Smart Program in Brebes Regency and 7 keyperson. The analytical tool used in this study is gap analysis and Analitycal Hierarchy Proccess (AHP) analysis. The results in this study indicate that the conditions and development of the implementation of the Smart Indonesia Program in Brebes Regency is quite good with the percentage of indicator application of 45%. Based on the results of the AHP analysis shows that the order of priority strategies for improving the Smart Indonesia Program in Brebes Regency are sequence, monitoring and evaluation, government policies, and human resources. Based on these priorities, in an effort to improve the Smart Indonesia Program in Brebes Regency, it is necessary to improve the mechanism for implementing the Smart Indonesia Program. Whereas the alternative priority in the Smart Indonesia Program Improvement strategy in Brebes Regency is that funds are channeled directly to the recipients of the Smart Indonesia Program. Penelitian ini bertujuan untuk mengetahui kondisi dan perkembangan penerapan Program Smart Indonesia dan strategi untuk meningkatkan Program Smart Indonesia di Kabupaten Brebes. Jenis penelitian ini adalah deskriptif kuantitatif dan deskriptif kualitatif. Data yang digunakan adalah data primer. Responden yang digunakan dalam penelitian ini adalah 100 siswa sekolah menengah / kejuruan yang menerima Program Indonesia Smart di Kabupaten Brebes dan 7 orang kunci. Alat analisis yang digunakan dalam penelitian ini adalah analisis kesenjangan dan analisis Analitycal Hierarchy Proccess (AHP). Hasil dalam penelitian ini menunjukkan bahwa kondisi dan perkembangan implementasi Program Smart Indonesia di Kabupaten Brebes cukup baik dengan persentase penerapan indikator 45%. Berdasarkan hasil analisis AHP menunjukkan bahwa urutan strategi prioritas untuk meningkatkan Program Indonesia Pintar di Kabupaten Brebes adalah urutan, pemantauan dan evaluasi, kebijakan pemerintah, dan sumber daya manusia. Berdasarkan prioritas ini, dalam upaya meningkatkan Program Smart Indonesia di Kabupaten Brebes, perlu untuk meningkatkan mekanisme untuk menerapkan Program Smart Indonesia. Sedangkan prioritas alternatif dalam strategi Peningkatan Program Smart Indonesia di Kabupaten Brebes adalah bahwa dana disalurkan langsung ke penerima Program Smart Indonesia.